I hate everyone, except you - Kelly, Clinton (Gallery Books, 2017)
A collection of essays by the moderator of "The Chew" charts his journey from a misfit youth to an awkward adult, exploring his haphazard experiences with 1980s porn, New Jersey's premiere water parks, his sister's cheerleading endeavors, and a life-threatening mud bath.